AKIBAT HUKUM HAK MENGUASAI TANAH OLEH ORANG ASING DENGAN MENGGUNAKAN NAMA ORANG LAIN (Studi Putusan No: 82/PDT.G/2013/PN.DPS) - Muhammad Sahroni (Universitas Islam Sumatera Utara, 2018)
Legal provisions confirm that foreigners cannot have land rights in Indonesia. As a result, foreign citizens who wish to own land in Indonesia do certain ways that are against the law to be able to own land in Indonesia. The method used by foreigners is by borrowing a name, where the foreigner is an investor and then makes a local person as a buyer to take further action to control land rights. However, the ownership of land rights is basically addressed to the foreign citizens. This means that in the practice of borrowing names related to the ownership of land rights for foreign citizens, there are efforts to deceive the government, namely by borrowing the names of local (Indonesian) people.As for the conclusion, the ownership of land rights for foreign citizens in Indonesia is only limited to the rights to use, unless otherwise determined by the government. The factor causing the ownership of land ownership rights by foreign citizens is due to legal smuggling by them of the land and building ownership in Indonesia, so that the ownership of the land and building rights in Indonesia by foreign citizens occurs with deviations from the applicable laws and regulations. The right to control land by people using other people's names has legal consequences on the land objects and the legal actions carried out by the parties. For the land objects, the land may fall to the state in accordance with Article 26 paragraph (2) of the Basic Agrarian Law. Meanwhile, the nominee agreement between a foreigner and the person whose name is borrowed is null and void.Keywords: Legal Consequences, Mastering Land Rights, Foreigners.